The Discourse on Language in International Relations - Akyesilmen, Nezir; Ishmeal, Mohammed (Wydawnictwo Naukowe WNPiD UAM, 2019)
Little has changed since Stanley Hoffman declared International Relations (IR) an American Social Science and John Hobson highlighted the “lack of value-free and universalist theories of inter-state relations.” Since the 1970s in particular, with the end of the Cold War and developments in Information and Communication Technologies (ICT), the discipline of IR has faced major challenges to its core conceptual and theoretical framework. Despite several systemic changes and the emergence of a new environment in international relations, the field is still heavily reliant on the old, inadequate and/or value-laden concepts of the early twentieth century. Moreover, the discipline has been overloaded by a set of Eurocentric and ethnocentric concepts which lead IR students to question its international character. It is debatable whether this is due to incompetence or misuse of language. This article aims to deconstruct mainstream and hegemonic concepts in IR in a constructive manner. This paper utilizes a qualitative method of discourse analysis to re-examine the relationship between the use of language and context, often taken for granted, which limits the understanding of the concepts used in the discipline of IR to promote innovation and progress in the field.

Niewiele się zmieniło od czasu, gdy Stanley Hoffman ogłosił, że stosunki międzynarodowe (IR) są amerykańską nauką społeczną, a John Hobson podkreślił „brak bezwartościowych i uniwersalistycznych teorii relacji międzypaństwowych.” W szczególności od 1970 r., wraz z końcem zimnej wojny oraz rozwojem technologii informacyjnych i komunikacyjnych (ICT), dyscyplina IR stanęła przed poważnymi wyzwaniami w stosunku do swoich podstawowych ram koncepcyjnych i teoretycznych. Pomimo szeregu zmian systemowych i pojawienia się nowego środowiska w stosunkach międzynarodowych, dziedzina ta nadal jest silnie uzależniona od starych, nieodpowiednich i/lub obciążonych wartością koncepcji z początku XX wieku. Co więcej, dyscyplina została przeciążona przez zestaw eurocentrycznych i etnocentrycznych koncepcji, które prowadzą studentów IR do kwestionowania jej międzynarodowego charakteru. Można dyskutować, czy wynika to z niekompetencji czy niewłaściwego używania języka. Artykuł ten ma na celu konstruktywną dekonstrukcję głównych i hegemonicznych koncepcji w IR. W pracy wykorzystano jakościową metodę analizy dyskursu, aby ponownie zbadać związek między użyciem języka i kontekstu, często uważaną za pewnik, co ogranicza rozumienie pojęć stosowanych w dyscyplinie IR w celu promowania innowacji i postępu w tej dziedzinie.
Dyskurs nad językiem w stosunkach międzynarodowych
Keywords: language; intellectual hegemony; periphery; multiculturalism; International Relations (IR); język; hegemonia intelektualna; peryferia; wielokulturowość; stosunki międzynarodowe (IR)